K2-30 b and K2-34 b: Two inflated hot Jupiters around solar-type stars - Lillo Box, J. (2016)
We report the discovery of the two hot Jupiters K2-30 b and K2-34 b. The two planets were detected during campaigns 4 and 5 of the extension of the Kepler mission, K2; they transit their main-sequence stars with periods of ~4.099 and ~2.996 days. Subsequent ground-based radial velocity follow-up with SOPHIE, HARPS-N, and CAFE established the planetary nature of the transiting objects. We analyzed the transit signal, radial velocity, and spectral energy distributions of the two systems to characterize their properties. Both planets (K2-30 b and K2-34 b) are bloated hot Jupiters (1.20 RJup and 1.22 RJup) around relatively bright (V = 13.5 and V = 11.5) slow rotating main-sequence (G8 and F9) stars. Thus, these systems are good candidates for detecting the Rossiter-MacLaughlin effect in order to measure their obliquity and for atmospheric studies.